2016
DOI: 10.1103/physrevb.93.035121
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking density functionals for hydrogen-helium mixtures with quantum Monte Carlo: Energetics, pressures, and forces

Abstract: An accurate understanding of the phase diagram of dense hydrogen and helium mixtures is a crucial component in the construction of accurate models of Jupiter, Saturn, and Jovian extrasolar planets. Though DFT based first principles methods have the potential to provide the accuracy and computational efficiency required for this task, recent benchmarking in hydrogen has shown that achieving this accuracy requires a judicious choice of functional, and a quantification of the errors introduced. In this work, we p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…In our recent work, we have demonstrated that for studying the high‐pressure solid hydrogen phase diagram, the BLYP XC functional is more accurate than most other semi‐local XC functionals. Independent studies of others have confirmed the superior accuracy of the used BLYP XC functional for the description of thermodynamic properties of high‐pressure hydrogen . Geometry and cell optimizations were performed using the Broyden–Fletcher–Goldfarb–Shanno quasi‐Newton algorithm with a convergence thresholds on the total energy and forces of 0.01 mRy and 0.1 mRy/Bohr, respectively, to guarantee convergence of the total energy to better than 1 meV/proton and the pressure to better than 0.1 GPa/proton.…”
Section: Methodsmentioning
confidence: 99%
“…In our recent work, we have demonstrated that for studying the high‐pressure solid hydrogen phase diagram, the BLYP XC functional is more accurate than most other semi‐local XC functionals. Independent studies of others have confirmed the superior accuracy of the used BLYP XC functional for the description of thermodynamic properties of high‐pressure hydrogen . Geometry and cell optimizations were performed using the Broyden–Fletcher–Goldfarb–Shanno quasi‐Newton algorithm with a convergence thresholds on the total energy and forces of 0.01 mRy and 0.1 mRy/Bohr, respectively, to guarantee convergence of the total energy to better than 1 meV/proton and the pressure to better than 0.1 GPa/proton.…”
Section: Methodsmentioning
confidence: 99%
“…For fixed nuclei positions, we have calculated the electronic energy using the QMCPACK [49,50] simulation package based on a single Slater-Jastrow wavefunction with single particle orbitals obtained from Quantum espresso [39] using the PBE functional (see Ref. [47,48] for further details).…”
Section: Hydrogen-helium Mixturesmentioning
confidence: 99%
“…In DFT simulations, however, a bottleneck is the exchange-correlation (XC) functional for which a variety of options exist, the accuracy of which is often poorly known, what limits the predictive power of the method. This requires tests against independent methods such as quantum Monte Carlo simulations for the electron component [4] or against electronion quantum Monte Carlo [70][71][72]. Also, the use of finite-temperature functionals was shown to be important [73,74] when the XC-contribution is comparable to the thermal energy, see Ref.…”
Section: Introductionmentioning
confidence: 99%